Challenges and opportunities of rewarding influencers in order to foster brand lift - the case of the brand kehl’s In Portugal - Moreira, Carolina Beatriz Franco Nunes (2020)
The objective of this thesis is to uncover the value of the use of influencers as a marketing tool, thoughthrough the case study of the skin care brand Kiehl’s Since 18511 in Portugal. The research focus on the activity of twelve influencers selected to help to promote Kiehl’s. More specifically, we explore the value added by each of the influencers. Through a longitudinal data collection and an analysis into the social media activity of the influencers, an attempt is made to measure the impact of this new marketing technique on the Brand Lift2. The research suggests that the influencers do not have a direct impact on the Brand Lift, but they can help potentialize the brand through the promotion of events, discounts and contests.